Dietary Enteromorpha Polysaccharide Enhances Intestinal Immune Response, Integrity, and Caecal Microbial Activity of Broiler Chickens - Wassie, Teketay; Lu, Zhuang; Duan, Xinyi; Xie, Chunyan; Gebeyew, Kefyalew; Yumei, Zhang; Yin, Yulong; Wu, Xin (Frontiers in Nutrition, 2021)
Marine algae polysaccharides have been shown to regulate various biological activities, such as immune modulation, antioxidant, antidiabetic, and hypolipidemic. However, litter is known about the interaction of these polysaccharides with the gut microbiota. This study aimed to evaluate the effects of marine algae Enteromorpha (Ulva) prolifera polysaccharide (EP) supplementation on growth performance, immune response, and caecal microbiota of broiler chickens. A total of 200 one-day-old Ross-308 broiler chickens were randomly divided into two treatment groups with ten replications of ten chickens in each replication. The dietary treatments consisted of the control group (fed basal diet), and EP group (received diet supplemented with 400 mg EP/kg diet). Results showed that chickens fed EP exhibited significantly higher (P < 0.05) body weight and average daily gain than the chicken-fed basal diet. In addition, significantly longer villus height, shorter crypt depth, and higher villus height to crypt depth ratio were observed in the jejunal and ileal tissues of chickens fed EP. EP supplementation upregulated the mRNA expression of NF-κB, TLR4, MyD88, IL-2, IFN-α, and IL-1β in the ileal and jejunal tissues (P < 0.05). Besides, we observed significantly higher (P < 0.05) short-chain volatile fatty acids (SCFAs) levels in the caecal contents of the EP group than in the control group. Furthermore, 16S-rRNA analysis revealed that EP supplementation altered gut microbiota and caused an abundance shift at the phylum and genus level in broiler chicken. Interestingly, we observed an association between microbiota and SCFAs production. Overall, this study demonstrated that supplementation of diet with EP promotes growth performance, improves intestinal immune response and integrity, and modulates the caecal microbiota of broiler chickens. This study highlighted the application of marine algae polysaccharides as an antibiotic alternative for chickens. Furthermore, it provides insight to develop marine algae polysaccharide-based functional food and therapeutic agent.